THE DETERMINANT IMPACTING FRUIT AND VEGETABLE CONSUMPTION AMONG FAMILIES IN MALUKU, INDONESIA - Arter Eliezer Sitepu; Pakpahan, Martina; Sarah Lidya Cicilia (The Indonesian Journal of Public Health, 2025)
Introduction: Consuming a minimum of 400 g of fruits and vegetables (FV) daily fulfills nutritional needs and diminishes the possibility of getting specific non-communicable diseases. In low or middle-income countries, about 80% of people consume fruits and vegetables below the WHO's recommendations, including Indonesia, where 93.6% of the population does so. In Indonesia, the annual per capita consumption of FV is only 35 kg; however, in Maluku, it is far lower at 7.78 kg per capita annually, below the Food and Agriculture Organization (FAO)’s objective of 75 kg per year. Aims: This study aims to identify the determinants that impact family behavior regarding FV consumption. Methods: This study took a cross-sectional approach. The purposive sampling chose a total of 398 families. The study employed a questionnaire that has passed validity and reliability tests, with Cronbach alpha >0.8. Results: The findings revealed that 192 (48%) respondents had enough knowledge, 253 (63.2%) had good access to fruits and vegetables, and 198 (49.5%) demonstrated good behavior. Furthermore, the chi-square test revealed that knowledge and family consumption of fruits and vegetables are correlated (p-value 0.001) as well as between FV availability and family consumption behavior (p-value 0.036). Conclusions: The study's findings serve as a road map for local governments, health institutions, and related parties seeking to ensure the availability of fruits and vegetables to meet the community's consumption demands. It also focuses on family-centered education to enhance FV consumption behavior.